2003
DOI: 10.1088/0957-0233/14/2/308
|View full text |Cite
|
Sign up to set email alerts
|

Crack detection and vertical deflection monitoring in concrete beams using plastic optical fibre sensors

Abstract: Plastic optical fibres have been employed to detect initial cracks, monitor post-crack vertical deflection and detect failure cracks in concrete beams subjected to flexural loading conditions. The intensity-based sensor system relies on monitoring the modulation of light intensity within the optical fibre as the sensor is loaded. The sensor design offers good signal stability and sensitivity to the monitored parameter and represents a cost-effective alternative to other more sophisticated health-monitoring sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 13 publications
0
46
0
2
Order By: Relevance
“…Kuang et al [13] conducted a series of flexural tests on scaled-specimens where the POF sensor was attached to the bottom surface of the concrete beams and demonstrated in their study that the POF sensor design used were of sufficient sensitivity to detect the presence of hair-line cracks. Figure 5 shows photomicrographs of the size of the cracks in the concrete relative to the POF.…”
Section: Applications Of Intensity-based Pof Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuang et al [13] conducted a series of flexural tests on scaled-specimens where the POF sensor was attached to the bottom surface of the concrete beams and demonstrated in their study that the POF sensor design used were of sufficient sensitivity to detect the presence of hair-line cracks. Figure 5 shows photomicrographs of the size of the cracks in the concrete relative to the POF.…”
Section: Applications Of Intensity-based Pof Sensorsmentioning
confidence: 99%
“…6. Plots showing the ability of the POF sensors in detecting the crack for a series of six scaled concrete specimens (after [13]). …”
Section: Applications Of Intensity-based Pof Sensorsmentioning
confidence: 99%
“…These moments corresponding to deflection ∆ cr , ∆ y , and ∆ u as can be seen in Figure 2. The technique adopted above is more convenient which give sufficient results in terms of M y evaluation instead of using moment-curvature relationship that need strain measurement of concrete and tensile reinforcement of the beam [22].…”
Section: Behaviour Of the Beam Test Specimensmentioning
confidence: 99%
“…The Fiber Bragg grating (FBG) sensor, due to its high sensitivity, resistance to electromagnetic interference, good durability, low cost, and more importantly capability of real-time monitoring, has become a widely accepted sensing alternative for strain [27][28][29], temperature [29][30][31], and possibly crack measurements [32,33] in civil engineering fields. Studies of using FBG sensors in crack detection on concrete and metallic structures had shown that distinguishable data alter could be observed when cracks initiated.…”
Section: Introductionmentioning
confidence: 99%